Advances in parasitology, Volume ninety four, Mathematical models neglected tropical diseases essential tools for control and elimination, Part B - Basáñez, Maria Gloria; Anderson, Roy M. (Academic Press, 2016)
Mathematic Modelling: Improving the Implementation, Monitoring and Evaluation of Interventions, Part B, the latest volume in the Advances in Parasitology series contains comprehensive and up-to-date reviews in the field of mathematic modeling and its implementation within parasitology. The series includes medical studies of parasites of major influence, such as Plasmodium falciparum and trypanosomes, along with reviews of more traditional areas, such as zoology, taxonomy, and life history, all of which shape current thinking and applications
Includes bibliographical references at the end of each chapters and index
Keywords: HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Evidenz-basierte Medizin; Innere Medizin; Mathematisches Modell; Medizin; Tropical medicine -- Mathematical models; Parasitic diseases -- Mathematical models